'Theory at the edge of empire'. (March 2022) - Martin, John Levi
Reed's intervention in theories of political power is considered, critiqued and continued: we may understand chains of authorization as stretching from sovereign to agent and back again, chains whose links may be called into question and repaired only via Goffmanian performance.